2012
DOI: 10.1095/biolreprod.111.093468
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Follicular Development Induced by Chronic Unpredictable Stress Is Associated with Growth and Differentiation Factor 9 and Gonadotropin in Mice1

Abstract: Chronic psychosocial stress negatively affects ovarian function. Ovarian follicular development is regulated by both pituitary-derived gonadotropins and intraovarian regulatory factors. To date, the suppressive effects of chronic stress on the ovary have been observed to be manifested mainly as an inhibition of gonadotropin release. It is not clear whether there are any other intraovarian regulatory mechanisms involved in this process. Growth and differentiation factor 9 (GDF9) is an important, oocyte-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…The open field activity of the mice in our study implicated that the mice were in an anxious emotional and psychological state after chronic unpredictable stress. These data is consistent with our previous study [9], [15]. Consistent with the previous report [14], the animal model in our study also showed signs of increased activity in the HPA axis, including increased CRH neurons in PVN of hypothalamus and corticosterone hypersecretion from adrenal.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The open field activity of the mice in our study implicated that the mice were in an anxious emotional and psychological state after chronic unpredictable stress. These data is consistent with our previous study [9], [15]. Consistent with the previous report [14], the animal model in our study also showed signs of increased activity in the HPA axis, including increased CRH neurons in PVN of hypothalamus and corticosterone hypersecretion from adrenal.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies by our group [9] and others [10] had found that chronic stress leads to follicular maldevelopment [9], [10]. A growing body of evidence demonstrated that chronic stress decreases the expression of BDNF in limbic structures in the central nervous system, which may contribute to mood disorder[11][13].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations